Redox post-translational modifications and their interplay in plant abiotic stress tolerance - Martí-Guillén, José M.; Pardo-Hernández, Miriam; Martínez-Lorente, Sara E.; Almagro, Lorena; Rivero, Rosa M. (Frontiers in Plant Science, 2022)
The impact of climate change entails a progressive and inexorable modification of the Earth's climate and events such as salinity, drought, extreme temperatures, high luminous intensity and ultraviolet radiation tend to be more numerous and prolonged in time. Plants face their exposure to these abiotic stresses or their combination through multiple physiological, metabolic and molecular mechanisms, to achieve the long-awaited acclimatization to these extreme conditions, and to thereby increase their survival rate. In recent decades, the increase in the intensity and duration of these climatological events have intensified research into the mechanisms behind plant tolerance to them, with great advances in this field. Among these mechanisms, the overproduction of molecular reactive species stands out, mainly reactive oxygen, nitrogen and sulfur species. These molecules have a dual activity, as they participate in signaling processes under physiological conditions, but, under stress conditions, their production increases, interacting with each other and modifying and-or damaging the main cellular components: lipids, carbohydrates, nucleic acids and proteins. The latter have amino acids in their sequence that are susceptible to post-translational modifications, both reversible and irreversible, through the different reactive species generated by abiotic stresses (redox-based PTMs). Some research suggests that this process does not occur randomly, but that the modification of critical residues in enzymes modulates their biological activity, being able to enhance or inhibit complete metabolic pathways in the process of acclimatization and tolerance to the exposure to the different abiotic stresses. Given the importance of these PTMs-based regulation mechanisms in the acclimatization processes of plants, the present review gathers the knowledge generated in recent years on this subject, delving into the PTMs of the redox-regulated enzymes of plant metabolism, and those that participate in the main stress-related pathways, such as oxidative metabolism, primary metabolism, cell signaling events, and photosynthetic metabolism. The aim is to unify the existing information thus far obtained to shed light on possible fields of future research in the search for the resilience of plants to climate change.